Analysis Role of Social Support in Mental Development of Athletes After Injury - Firdaus Abdul Arasy; Herman Subarjah; Tono Haryono; Ridha Mustaqim (Journal of Physical Education Health and Sport, 2025)
Sports injuries not only affect physical condition, but also influence athletes’ mental development during the recovery process and return to training. This study aims to analyse the relationship between social support and athletes mental development after injury, as well as to examine differences in mental development based on the severity of the injury. A quantitative approach with a correlational design was used by distributing an online questionnaire to 51 athletes from various sports, including athletes undergoing rehabilitation at the Sport Therapist Injury Laboratory,Universitas Pendidikan Indonesia. The instruments used were the Multidimensional Scale of Perceived Social Support (MSPSS) and the Injury Psychological Readiness to Return to Sport (I-PRRS). Data analysis was performed using parametric statistical techniques. The result revealed a weak positive connection between social support and post-injury mental development (r = 0.235), which was not statistically significant (p > 0.05) and no significant differences across injury severity levels (F = 2.175; p > 0.05). These findings indicate that variations in injury severity and perceived social support do not significantly influence athletes’ psychological readiness to return to sport.Overall, the findings indicate that internal psychological factors have a greater influence on mental recovery after injury than external help or injury classification. The results of the study showed that social support had no significant relationship with the mental development of athletes after injury, and there were no differences in mental development based on the severity of the injury. These findings confirm that internal psychological contributions play a more important role in the mental recovery of athletes.